Editorial - Power, Deborah (2017)
In a globally changing climate and with the alarming loss of biodiversity Comparative Endocrinology becomes ever more relevant as a scientific discipline. The comparative endocrinologist continues to be at the frontline of scientific endeavour trying to understand the myriad complexities of life forms on earth by looking at the regulatory factors that underpin key events in an organisms’ life and ensure maintenance of homeostasis and species survival.